Development in Costa Rica: The key role of agriculture - Celis, Rafael; Lizano, Eduardo (International Food Policy Research Institute, 1995)
Costa Rica is a relatively small country (50,000 square kilometers) with a population of only 2.7 million inhabitants. Its economy is small (GDP $4.7 billion), relatively open (annual imports account for 35 percent of GDP), and relatively poor (per capita yearly income is $1,600). Demographic and economic growth during the period after World War II was extremely rapid: between the periods 1950-52 and 1975-77 its population doubled, as did real per capita income. The 1980s, however, might well be labeled a lost decade. After the second oil-price shock at the end of the 1970s, the economy fell into its worst crisis in more than half a century. The effort to resolve the crisis consumed most of the available resources for several years. It has only been in the past few years that the pace of economic growth has more or less returned to a satisfactory level. Still, economic growth, real per capita income, and affluence indicators remain below precrisis levels.